1981
DOI: 10.1126/science.213.4510.905
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides: Insecticides and Fungicides Are Chitin Synthesis Inhibitors

Abstract: Several important groups of fungicides and insecticides are specific inhibitors of chitin synthesis in a Phycomyces enzyme system and in insect organ cultures. The recently discovered benzoylphenylurea insecticides, which prevent chitin synthesis in insect tissues, are apparently not direct-acting chitin synthetase inhibitors. These insecticides may prevent insect chitin synthesis by interfering with the proteolytic activation of the chitin synthetase zymogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(35 citation statements)
references
References 13 publications
2
33
0
Order By: Relevance
“…This interpretation would be consistent with the proposal of Leighton et al (1981), who suggested that diflubenzuron may inhibit a protease-induced activation of the zymogen form of chitin synthase. It would be consistent also with the results of Horst (1981), who found that microsomal preparations from larvae of the brine shrimp (Artemia salina) show reduced capacity for chitin synthesis following pre-incubation with diflubenzuron.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This interpretation would be consistent with the proposal of Leighton et al (1981), who suggested that diflubenzuron may inhibit a protease-induced activation of the zymogen form of chitin synthase. It would be consistent also with the results of Horst (1981), who found that microsomal preparations from larvae of the brine shrimp (Artemia salina) show reduced capacity for chitin synthesis following pre-incubation with diflubenzuron.…”
Section: Discussionsupporting
confidence: 80%
“…Similarly, in a microsomal chitin synthase system prepared from extracts of larvae of the brine shrimp (Artemia salina), inhibition was obtained only after preincubation of the system with diflubenzuron (Horst 1981). Recently, Leighton et al (1981) proposed that diflubenzuron acts indirectly on chitin synthase, by inhibiting a proteolytic enzyme required for the activation of chitin synthase from a zymogen form.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies with cellfree insect extracts which exhibit chitin synthase activity (Cohen and Casida 1980b;Mayer et al 1980) diflubenzuron was found to have no inhibitory effect. Leighton et al (1981) have proposed that diflubenzuron acts indirectly on chitin synthase by inhibiting a proteolytic enzyme required for its activation from the zymogen form.…”
Section: Discussionmentioning
confidence: 99%
“…Although the authors did not recognize that an inhibition of chitin synthesis was responsible for these effects, the potential for these agents as pesticides and fungicides was ultimately recognized and described. While the action of the benzoylphenyl ureas on insect cuticles was claimed to be identical to that seen with polyoxin D (227), others thought that the specific effects of this class of agent were a result of an inhibition of serine protease activity that blocked activation of the chitin synthetase zymogen (150). These and other chymotrypsin inhibitors were demonstrated to prevent chitin synthesis in a cockroach system.…”
Section: Compounds Active Against Fungal Cell Walls Inhibitors Of Chimentioning
confidence: 99%